2018
DOI: 10.1093/humrep/dey048
|View full text |Cite
|
Sign up to set email alerts
|

The psychological well-being and prenatal bonding of gestational surrogates

Abstract: STUDY QUESTIONHow does the psychological well-being and prenatal bonding of Indian surrogates differ from a comparison group of mothers?SUMMARY ANSWERSurrogates had higher levels of depression during pregnancy and post-birth, displayed lower emotional connection with the unborn baby, and greater care towards the healthy growth of the foetus, than the comparison group of mothers.WHAT IS ALREADY KNOWNStudies in the West have found that surrogates do not suffer long-term psychological harm. One study has shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 34 publications
2
34
0
3
Order By: Relevance
“…The included studies were mainly conducted in the US (10 papers) [80,[84][85][86][87][88][89][90][91][92] and in Europe (nine papers in Italy [93][94][95][96][97][98][99][100][101], four in Sweden [76,[102][103][104], two in Germany [105,106], one in the Netherlands [22], one in France [107], one in England [79], one in Belgium [108], and one in Portugal [75]). Four studies were carried out in Japan [81,[109][110][111], two in Australia [112,113], two in Iran [74,114], two in Turkey [78,115], one in India [116], one in Israel [117], one in Chile [118], one in Brazil [119], and one in Korea [120] (Figure 2). All the articles were published between 1988 and 2019 (…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies were mainly conducted in the US (10 papers) [80,[84][85][86][87][88][89][90][91][92] and in Europe (nine papers in Italy [93][94][95][96][97][98][99][100][101], four in Sweden [76,[102][103][104], two in Germany [105,106], one in the Netherlands [22], one in France [107], one in England [79], one in Belgium [108], and one in Portugal [75]). Four studies were carried out in Japan [81,[109][110][111], two in Australia [112,113], two in Iran [74,114], two in Turkey [78,115], one in India [116], one in Israel [117], one in Chile [118], one in Brazil [119], and one in Korea [120] (Figure 2). All the articles were published between 1988 and 2019 (…”
Section: Resultsmentioning
confidence: 99%
“…Considering the 45 studies included in the current review, 31 found a negative association between prenatal attachment and perinatal depression [22,74,75,81,84,86,[89][90][91][92]95,[97][98][99]101,102,[104][105][106][107][108][110][111][112][114][115][116][117][118][119][120], while a positive relation between perinatal depression and some dimensions of antenatal attachment was identified in three studies [94,102,106]. Thirteen studies did not highlight significant associations between these variables [76,[78][79][80]85,87,88,93,96,100,103,109,113].…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a woman cannot become a surrogate mother by providing her own gametes (unfertilised eggs). (Lamba et al 2018) When is surrogacy permitted? As per the Bill, only altruistic surrogacy will be permitted in India, in cases where either or both members of the couple suffer from infertility, of which the certificate of essentiality is proof.…”
Section: Surrogate Mothermentioning
confidence: 99%